Performance Analysis of Genetic Zone Routing Protocol Combined With Vertical Handover Algorithm for 3G-WiFi Offload - Setiyo Budiyanto; Muhammad Asvial; Dadang Gunawan (Journal of ICT Research and Applications, 2014)
In the deployment scenario of multiple base stations there is usually a deficiency in the routing protocols for load balancing in the wireless network. In this study, we propose a routing algorithm that can be implemented inMobile Adhoc Networks (MANETs) as well as third-generation (3G)"“Wireless Fidelity (WiFi) offload networks. We combined the Genetic Zone Routing Protocol (GZRP) with the Vertical Handover (VHO) algorithm in a 3G"“WiFioffload network with multiple base stations. Simulationresults show thatthe proposed algorithm yields improvement in the received signal strength(which is increased up to 25 dBm), user throughput (which is approximately 1 Mbps-2.5 Mbps), and data rate (which is increased up to 2.5 Mbps).